Queer & trans advocacy in the community college - Johnson, Joshua Moon; Mitchell, Emilie; Watson, Lemuel W. (Emerald Publishing Limited : IAP/Information Age Publishing, Inc., 2022)
"LGBTQ advocacy and support continues to be a priority in the U.S. higher education, and recent research shows this as a critical population who continues to be marginalized and mistreated on college and university campuses. Over the last few decades there has been significant research describing how LGBTQ students experience higher education and highlighting that these students are not graduating or succeeding at the same rates as the general population. However, few if any research studies or articles address LGBTQ advocacy on community college campuses. There are more than 1,000 community colleges in the U.S. Even with the extraordinary number of students that the community college system educates only ten institutions nationally have paid staff to provide LGBTQ services to students. That being said, community colleges are now putting a larger emphasis on understanding and supporting this community. For example, The California Community College (CCC) system's 115 colleges now require all campuses to create a plan on how to improve success rates of LGBTQ students. The CCC is the largest higher education system in the country serving over 2.1 million students. This comprehensive practitioner focused book will combine relevant research and guidance on practices to aid colleges in establishing services and programs to build effective LGBTQ services on their college campuses"-- Provided by publisher.
Keywords: Sexual minority college students -- United States.; Community college students -- Political activity -- United States.; Community colleges -- United States.; Education -- Schools -- Levels -- Higher.; Relating to LGBTQ+ people.; Higher education, tertiary education.; elektronické knihy; electronic books